2017
DOI: 10.1007/s11356-017-8951-3
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic pigments and peroxidase activity of Lepidium sativum L. during assisted Hg phytoextraction

Abstract: The study was conducted to evaluate metabolic answer of Lepidium sativum L. on Hg, compost, and citric acid during assisted phytoextraction. The chlorophyll a and b contents, total carotenoids, and activity of peroxidase were determined in plants exposed to Hg and soil amendments. Hg accumulation in plant shoots was also investigated. The pot experiments were provided in soil artificially contaminated by Hg and/or supplemented with compost and citric acid. Hg concentration in plant shoots and soil substrates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Lepidium sativum L. is an edible plant which aqueous extracts have been used in the medicine. Therefore, its use in the soil reclamation processes may be doubtful due to the risk of transferring pollutants to the food chain . The risk for human is limited by the exclusion of highly contaminated sites from agricultural use, and by the monitoring of potential pathways of spreading pollutants .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lepidium sativum L. is an edible plant which aqueous extracts have been used in the medicine. Therefore, its use in the soil reclamation processes may be doubtful due to the risk of transferring pollutants to the food chain . The risk for human is limited by the exclusion of highly contaminated sites from agricultural use, and by the monitoring of potential pathways of spreading pollutants .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, its use in the soil reclamation processes may be doubtful due to the risk of transferring pollutants to the food chain . The risk for human is limited by the exclusion of highly contaminated sites from agricultural use, and by the monitoring of potential pathways of spreading pollutants . Precautions are taken to ensure that remediation of soils contaminated by trace metals with the use of edible plants are not contributed to the formation of any risk for human.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of BPOD is aimed at Н 2 О 2 destruction and counteracting oxidative stress caused by C. ohridella attack. It is shown that changes in physiological processes of plant leaves under adverse conditions, particularly photosynthesis correlates with peroxidase activity (Kim et al, 2010;Smolinska, 2017). This enzyme destroys ROS and protects chloroplasts from damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is a fast-growing annual herbaceous plant belonging to the Brassicaceae family with a global diffusion; it is widely used both as an edible plant than phototherapeutics purposes [16]. Its high sensitivity to phytotoxic substances makes it suitable for biological test [17,18].…”
Section: Introductionmentioning
confidence: 99%